Pengaruh Aksesibilitas Wisata Terhadap Jumlah Kunjungan Wisatawan Di Destinasi Wisata Candi Borobudur - Ayun, Fira Khurota; Prasetyo, Danang; Nusanto, Tri Suyud (JURNAL DESTINASI PARIWISATA, 2024)
The Borobudur Temple's accessibility and facilities, which are essential for the growth of tourism, are impacted by the number of visitors who come here. The purpose of this study is to clarify the relationship between accessibility and the number of visitors to Borobudur Temple. The accessibility scale and the tourist visitation scale are the research tools used in this study. A total of 100 respondents were selected by chance selection. Tourist interviews, questionnaires, and observations were used in the data collecting process. Among the analytical techniques used are classical assumption testing, validity assessment, reliability evaluation, hypothesis testing, and basic linear regression. The results show that accessibility has a substantial partial impact on tourist visits (t-score of 4.174, p-value 0.000). A value of 0.389 indicates that the presence of tourists affects accessibility, according to hypothesis testing. Keywords: accessibility, number of visits, borobudur temple